Researching and designing the structure of Step-Up DC–DC Converters in solar cell power source converter - Nguyen, Duc Minh; Trinh, Trong Chuong; Dao, Huy Du (Journal of Military Science and Technology, 2022)
Step-Up DC–DC Converters in the solar cell system is designed to have consistent input voltage with the output voltage of the solar panel (usually in the range 24V-40V). This converter has a variation coefficient of voltage suitable for the load, compact size, high voltage variation ratio, large circuit efficiency. At the same time, DC/DC components need to be common to suit replication, suitable for many different origin solar panels integrated into the DC/DC unit input. In that view, the structure of Step-Up DC–DC Converters needs to have multiple inputs that may have different voltages in the range consistent the output voltage of the battery plate, the loss in the circuit should be reduced to a minimum, the undulating current through the inductor is low, the output voltage is balanced, stable. If the above technical problems can be solved, they will also contribute to solving the challenges posed for Step-Up DC–DC Converters in general and for solar cell power sources in particular. This paper presents the results of the design and test manufacturing of structure of a new Step-Up DC–DC Converters applied in the solar cell power source converter. Simulation results show: DC/DC booster efficiency reaches 95.07%.